Wild Treasures: reflections on Natural World Heritage Sites in Asia - Bindra, Prerna Singh; Ghosh, Sonali(ed.); Roy, Anuranjan(ed.) (New Delhi Wildlife Institute of India, 2019)
The World Natural Heritage Sites protect over 286 million hectares of land sea, including trans boundary sites, signifying that heritage sites belong to all peoples of the world, irrespective of the territory on which they are located.
Keywords: Reflections; Asia